KARAKTERISTIK SPASIOTEMPORAL KEKERINGAN METEOROLOGI DI KABUPATEN GORONTALO TAHUN 1981-2016 - Syahrizal Koem (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Drought is one of the natural disasters that can cause disadvantages, especially in the agricultural sector. Gorontalo Regency is the corn production center, yet it has high vulnerability and low adaptive capacity towards the climate change. In addition, its vulnerability to the impact of drought is seen from the high potential for environmental damage, the disadvantages due to the drought and the potential of the population exposed to drought. Standardized Precipitation Index (SPI) is the estimator tool employed to assess the severity of the drought. This study utilized monthly rainfall data from 17 stations in Gorontalo Regency and 2 stations outside Gorontalo Regency during the period of 1981-2016. The SPI values were calculated by utilizing DrinC software and spatial interpolation of drought using ArcGIS software. The result shows that the longest time of drought occurred in 1982, 1986, 1997 and 2015 due to El Nino phenomenon with moderate and strong category with long duration. Further, analysis result in the last four decades reveals that the worst drought occurred in 1982. Based on the result of frequency analysis on the SPI-3, SPI-6 and SPI-12 time scales, drought is frequently taken place in western regions. Thus, this result can be a reference in managing the water resources in Gorontalo Regency. The plan in the commodity-based agriculture sector can be developed since the result of spatial analysis indicates that SPI can identify the diversity of drought severity. It is necessary to place the climate change scenarios in order to prepare the adaptation and mitigation measures of drought impacts due to the uncertainty of future climate conditions. This is very helpful to provide an idea about the dynamics of drought.